2019
DOI: 10.1038/s41598-019-52046-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk of breast cancer in women with non-lactational mastitis

Abstract: Little is known regarding the association of non-lactational mastitis women with breast cancer risk. This population-based cohort study examined the breast cancer risk in women with non-lactational mastitis. We identified 3,091 women with non-lactational mastitis between 2000 and 2011 using the Taiwan National Health Insurance Research Database. We performed 1:4 propensity score matching by age, socioeconomic status and comorbidities and identified 12,364 women without non-lactational mastitis. The mean age of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…In addition, women who had comorbidity, such as hyperlipidemia, had an increased risk of breast cancer. Our findings are consistent with previous studies [13,14]. In their 2009 cohort study, Lambe et al identified from their database 8411 women who had a diagnosis of mastitis.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, women who had comorbidity, such as hyperlipidemia, had an increased risk of breast cancer. Our findings are consistent with previous studies [13,14]. In their 2009 cohort study, Lambe et al identified from their database 8411 women who had a diagnosis of mastitis.…”
Section: Discussionsupporting
confidence: 93%
“…When women with breast cancer were compared with those who had no recorded mastitis, the incidence rate of breast cancer was higher in women with mastitis [13]. Another study conducted by Chang et al identified that women with nonlactational mastitis faced a higher risk of breast cancer [14], which is similar to our results. In addition, our study focused on women aged ≥40.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The insurance premium was divided into 4 subgroups: 0 to 15 840 new Taiwan dollars (NTD) (equivalent to 0 to 528 United States dollars [USD]), 15 841 to 28 800 NTD (528 to 960 USD), 28 801 to 45 800 NTD (960 to 1526 USD), and >45 800 NTD (>1526 USD) per month 22 . We set 15 840 NTD as the low socioeconomic status cutoff point because it is the government‐regulated minimum salary specified for a full‐time worker in Taiwan 22 .…”
Section: Methodsmentioning
confidence: 99%
“…The insurance premium was divided into 4 subgroups: 0 to 15 840 new Taiwan dollars (NTD) (equivalent to 0 to 528 United States dollars [USD]), 15 841 to 28 800 NTD (528 to 960 USD), 28 801 to 45 800 NTD (960 to 1526 USD), and >45 800 NTD (>1526 USD) per month 22 . We set 15 840 NTD as the low socioeconomic status cutoff point because it is the government‐regulated minimum salary specified for a full‐time worker in Taiwan 22 . The NHRI stratified all townships and city districts in Taiwan into 7 urbanization levels based on population density (people/km 2 ), population ratio of habitants with higher educational degree, elder older than 65 years, and agriculture and the number of physicians per 100 000 people.…”
Section: Methodsmentioning
confidence: 99%